2018
DOI: 10.1128/mbio.01712-17
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Function of Structured N-Terminal and Unstructured C-Terminal Segments of Mycobacterium tuberculosis PPE37 Protein

Abstract: Pathogens frequently employ eukaryotic linear motif (ELM)-rich intrinsically disordered proteins (IDPs) to perturb and hijack host cell networks for a productive infection. Mycobacterium tuberculosis has a relatively high percentage of IDPs in its proteome, the significance of which is not known. The Mycobacterium-specific PE-PPE protein family has several members with unusually high levels of structural disorder and disorder-promoting Ala/Gly residues. PPE37 protein, a member of this family, carries an N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…It was recently reported that PPE37 is exported, with the protein found primarily in the cell membrane fraction, and that it possesses a eukaryotic-type signal sequence from residues 1 to 40, although the details for how the signal sequence was determined were not reported (31). We analyzed the M. tuberculosis PPE37 sequence using SignalP, TatP, LipoP, and TargetP to predict potential secretion signals.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was recently reported that PPE37 is exported, with the protein found primarily in the cell membrane fraction, and that it possesses a eukaryotic-type signal sequence from residues 1 to 40, although the details for how the signal sequence was determined were not reported (31). We analyzed the M. tuberculosis PPE37 sequence using SignalP, TatP, LipoP, and TargetP to predict potential secretion signals.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PPE37 does not have a conventional signal peptide that can be detected by the SignalP, TatP, or LipoP algorithm, but the higher score than nonsecretory proteins and the cleavage site predictions suggest that it may possess a nonclassical signal peptide. As PPE37 has two transmembrane domains and as the protein was detected in the cell membrane fraction (31), it is likely to be an integral membrane protein. Interestingly, the cleavage site predictions occur either in the amino acids deleted from the BCG PPE37 protein or immediately adjacent to the deletion, suggesting that the BCG PPE37 protein might be processed differently.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations